Pengaruh Intensitas Penggunaan Media Sosial terhadap Etika Berkomunikasi Siswa Sekolah Dasar Negeri 1 Sugihrejo - Rahmatika, Noviana Dwi; Junaidi, Mahbub; Sholihah, Khotimatus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid growth of social media has influenced the communication patterns of elementary school students, making it important to examine its relationship with communication ethics. This study aimed to analyze the effect of social media use intensity on the communication ethics of students at SD Negeri 1 Sugihrejo. A quantitative survey design was employed involving 30 fourth-, fifth-, and sixth-grade students selected using total sampling. Data were collected through questionnaires, interviews, observations, and documentation, and analyzed using descriptive statistics, validity and reliability tests, normality testing, simple linear regression, t-test, and coefficient of determination. The results showed that the intensity of social media use was relatively high with a mean score of 75.43, while students' communication ethics were categorized as good with a mean score of 79.10. Simple linear regression analysis produced a regression coefficient of 0.440 with a significance value of 0.104 (p>0.05), indicating that the intensity of social media use had no significant effect on students' communication ethics. The coefficient of determination (R²) was 0.092, indicating that social media use intensity explained only 9.2% of the variance in communication ethics, while the remaining 90.8% was influenced by other factors beyond this study. These findings suggest that students' communication ethics are more strongly influenced by character education, family environment, and school culture than by the intensity of social media use